Veiled threats: women and global jihad - Bloom, Mia (Cornell University Press, 2025)
Veiled Threats challenges the idea that women in violent terrorist groups lack agency. Too often, these women are assumed to be controlled by men: their fathers, their husbands, or some other male relative. Mia Bloom contests this narrow understanding. Although extremist groups often control different aspects of women's lives, including their religious obligations or dress, jihadi women have asserted themselves in myriad ways. Bloom interrogates the prevailing perceptions about women's involvement in violent extremism exclusively as victims: manipulated, drugged, or coerced. Following her pioneering work on women in Bombshell, Bloom lifts the veil of the secret world of women in jihadi groups to provide a nuanced and complex explanation of their motivations and challenge misperceptions about women's agency. Veiled Threats explores the range of roles of the women involved in jihad - not only across secular and religious groups but within affiliated religious groups - and examines how these extremist groups have used rape as a weapon of war. Bloom explains how women are used and abused, deployed and destroyed, and the many ways in which their roles in terrorism have evolved over the past three decades.